Blockade of sodium‑calcium exchanger via ORM-10962 attenuates cardiac alternans. (April 2021) - Szlovák, Jozefina; Tomek, Jakub; Zhou, Xin; Tóth, Noémi; Veress, Roland; Horváth, Balázs; Szentandrássy, Norbert; Levijoki, Jouko; Papp, Julius Gy.; Herring, Neil; Varró, András; Eisner, David A.; et al.
Abstract: Repolarization alternans, a periodic oscillation of long-short action potential duration, is an important source of arrhythmogenic substrate, although the mechanisms driving it are insufficiently understood. Despite its relevance as an arrhythmia precursor, there are no successful therapies able to target it specifically. We hypothesized that blockade of the sodium‑calcium exchanger (NCX) could inhibit alternans. The effects of the selective NCX blocker ORM-10962 were evaluated on action potentials measured with microelectrodes from canine papillary muscle preparations, and calcium transients measured using Fluo4-AM from isolated ventricular myocytes paced to evoke alternans. Computer simulations were used to obtain insight into the drug's mechanisms of action. ORM-10962 attenuated cardiac alternans, both in action potential duration and calcium transient amplitude. Three morphological types of alternans were observed, with differential response to ORM-10962 with regards to APD alternans attenuation. Analysis of APD restitution indicates that calcium oscillations underlie alternans formation. Furthermore, ORM-10962 did not markedly alter APD restitution, but increased post-repolarization refractoriness, which may be mediated by indirectly reduced L-type calcium current. Computer simulations reproduced alternans attenuation via ORM-10962, suggesting that it is acts by reducing sarcoplasmic reticulum release refractoriness. This results from the ORM-10962-induced sodium‑calcium exchanger block accompanied by an indirect reduction in L-type calcium current. Using a computer model of a heart failure cell, we furthermore demonstrate that the anti-alternans effect holds also for this disease, in which the risk of alternans is elevated. Targeting NCX may therefore be a useful anti-arrhythmic strategy to specifically prevent calcium driven alternans. Graphical abstract: Unlabelled Image Highlights: Cardiac alternans is a major proarrhythmic phenomenon with no specific treatment. We demonstrate that NCX blockade via ORM-10962 attenuates alternans. Three distinct morphological types of APD alternans observed. Human cardiac simulations provide a mechanism of alternans attenuation by ORM-10962. This is mainly due to reduced refractoriness of calcium cycling in the SR.